PERAN GURU DALAM PENGEMBANGAN KURIKULUM YANG RESPONSIF DI MARKAZUL QURAN BUKITTINGGI - Rio Friyadi; Iswantir (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to explore innovations in Islamic education curriculum development in overcoming ethical challenges at Markazul Quran Bukittinggi and the role of teachers in developing a responsive curriculum at Markazul Quran Bukittin. Innovation in curriculum development is considered a key parameter for assessing the success and quality of Islamic religious education in overcoming the technological ethical dilemmas faced by students. It is necessary to remember that the curriculum is a dynamic entity that is always developing, keeping up with the times and the needs of society. Therefore, an educational institution which is part of society must always see the development of society as a source of learning as a consideration in preparing the curriculum development of its institution or institutions, understanding the use of social media, digital security, and the impact of technology on Islamic values ​​( Hadith and Al-Quran). The method that the author uses in research is library research. The results of this research show that innovative Islamic religious education curriculum development can overcome the challenges of student education at Markazul Quran Bukittinggi.